Combating climate change in Malaysia: critical appraisal on Sukuk as an Islamic social finance instrument - Yusof, Siti Ainatul Mardhiah; Mohd. Zain, Nor Razinah; Hasan, Aznan; Engku Ali, Engku Rabiah Adawiah (2020)
Sukuk are majorly used to raise funds in a large scale for the purpose of developments. With the increase of interest for responsible finance and investment, sukuk are used to meet such interests from the stakeholders. Instead of only looking for development purposes, Muslim scholars proposed that sukuk could be used for many other different purposes. An innovation of sukuk i.e. green sukuk has played a prominent role in financing infrastructure and renewable energy projects. With the introduction of Sustainable Development Goals (SDGs) by the United Nations in 2015 that strategize to be a blueprint to achieve sustainable future for all, green sukuk are looked up to as one of the most potential instruments that can be used in achieving such SDGs. Green sukuk stand with an advantage of a Shariah-compliance financing instrument that not only meet the demands from the investors and stakeholders; but also, it is able to provide a better alternative in a term of social finance discourse. Looking closely into the initiative in combating climate change in Malaysia, this research qualitatively investigates the potential and roles of green sukuk in leading the trend in eco-friendly investments and development projects. As a finding, there is a positive trend among investors towards green sukuk that are based on eco-friendly investments and development projects.